Electron Energy-Loss Spectroscopy in the Electron Microscope - Egerton, R.F. (Springer US : Imprint: Springer, 2011)
Within the last 30 years, electron energy-loss spectroscopy (EELS) has become a standard analytical technique used in the transmission electron microscope to extract chemical and structural information down to the atomic level.  In two previous editions, Electron Energy-Loss Spectroscopy in the Electron Microscope has become the standard reference guide to the instrumentation, physics and procedures involved, and the kind of results obtainable. Within the last few years, the commercial availability of lens-aberration correctors and electron-beam monochromators has further increased the spatial and energy resolution of EELS. This thoroughly updated and revised Third Edition incorporates these new developments, as well as advances in electron-scattering theory, spectral and image processing, and recent applications in fields such as nanotechnology. The appendices now contain a listing of inelastic mean free paths and a description of more than 20 MATLAB programs for calculating EELS data. Considered the "Bible of EELS" Presents the only in-depth, single-author text for the still-expanding field of TEM-EELS Responds to many requests for the first new edition of this classic work since 1996 Includes discussion of new spectrometer and detector designs, together with spectral-analysis techniques such as Bayesian deconvolution and multivariate statistical analysis Provides extended discussion of anisotropic materials, retardation effects, delocalization of inelastic scattering, and the simulation of energy-loss fine structure. Describes recent applications of EELS to fields such as nanotechnology, electronic devices and carbon-based materials. Offers extended coverage of radiation damage and delocalization as limits to spatial resolution. From reviews of the first and second edition: "The text....contains a wealth of practical detail and experimental insight....This book is an essential purchase for any microscopist who is using, or planning to use, electron spectroscopy or spectroscopic imaging." – JMSA "Provides the advanced student with an indispensible text and the experienced researcher with a valuable reference." -- American Scientist.